Biosynthesis And Characterization Of Poly(3-Hydroxybutyrate-Co-4-Hydroxybutyrate) Copolymer From Cupriavidus Sp. Usmahm13 - Ramachandran, Hema (2013)
Production of poly(3-hydroxybutyrate-co-4-hydroxybutyrate) [P(3HB-co-4HB)] using combination of waste glycerine and carbon precursor by bacteria is still very limited. Therefore, this research was conducted to (i) isolate and identify a bacterium that able to produce high PHA content and 4HB monomer composition, (ii) explore the ability of the bacterium to produce P(3HB-co-4HB) using various inexpensive and renewable carbon sources, (iii) optimize the P(3HB-co-4HB) copolymer production using glycerine pitch through shake-flask fermentation using response surface methodology (RSM) and (iv) evaluate the material characteristics of the P(3HB-co-4HB) copolymers with various 4HB monomer compositions. In this study, a novel yellow-pigmented bacterium which exhibited ability of producing P(3HB-co-4HB) copolymer was successfully isolated from Perak, Malaysia and designated as Cupriavidus sp. USMAHM13. Based on the phenotypic and genotypic analyses, it could be suggested that Cupriavidus sp. USMAHM13 represents a novel species within the genus Cupriavidus. Preliminary screening of carbon sources for biosynthesis of P(3HB-co-4HB) copolymer by Cupriavidus sp. USMAHM13 revealed that high 4HB monomer composition (43 mol%) with cell dry weight and PHA content of 6.0 g/l and 49 wt%, respectively was achieved through combination of glycerine pitch (5 g/l) and 1,4-butanediol (5 g/l) via one-stage cultivation.